Depression Management Education in Improving the Quality of Life of Patients with Type 2 Diabetes Mellitus at Grandmed Hospital - Tati Murni Karokaro; Sukarnawan Sukarnawan; Ratna Limbeng (JURNAL PENGMAS KESTRA (JPK), 2026)
Diabetes mellitus (DM) is a disease that often leads to physical health complications and adversely affects the psychological well-being of those living with the condition. Long-term treatment, lifestyle modifications, and concerns about disease-related complications may increase the risk of depression, which in turn can negatively impact patients’ quality of life. Limited knowledge regarding depression and its management often leads patients to experience psychological difficulties during the course of treatment. This community service program aimed to improve the knowledge of patients with T2DM regarding depression and depression management as an effort to support a better quality of life. The program was implemented using an educational-participatory approach through health education sessions, interactive discussions, and question-and-answer activities. Evaluation was used pre-test and post-test involving 20 patients with T2DM at Grandmed Hospital, Lubuk Pakam. The instruments included a knowledge questionnaire, observation sheets, educational leaflets, and presentation materials. The results showed that most participants were female (55%), aged 41–49 years (40%), experienced moderate depression (50%), and had poor quality of life (50%). Following the educational intervention, the mean knowledge score increased from 58.5 ± 11.2 to 84.0 ± 8.7, representing an improvement of 25.5 points. Participant satisfaction evaluation revealed that 75.0% were very satisfied, 20.0% were satisfied, and 5.0% were moderately satisfied with the program. These results indicate that depression management education was effective to improve participants’ knowledge and was well accepted as a strategy to support better quality of life among patients with Type 2 Diabetes Mellitus.